2004
DOI: 10.1128/jvi.78.19.10747-10754.2004
|View full text |Cite
|
Sign up to set email alerts
|

Entry and Transcription as Key Determinants of Differences in CD4 T-Cell Permissiveness to Human Immunodeficiency Virus Type 1 Infection

Abstract: Isolated primary human cells from different donors vary in their permissiveness-the ability of cells to be infected and sustain the replication of human immunodeficiency virus type 1 (HIV-1). We used replicating HIV-1 and single-cycle lentivirus vectors in a population approach to identify polymorphic steps during viral replication. We found that phytohemagglutinin-stimulated CD4؉ CD45RO ؉ CD57 ؊ T cells from healthy blood donors (n ‫؍‬ 128) exhibited a 5.2-log-unit range in virus production. For 20 selected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…However, in our ex vivo tissues, no infection with any of the primary R5 HIV-1 isolates affected the levels of the 16 measured cy- tokines/chemokines. Earlier, similar results were reported for an R5 laboratory strain and for recombinant viruses carrying R5 Envs, whereas an X4 strain significantly changed chemokine release (9,27). However, one recent study (8) has suggested that R5 HIV-1 infection of fetal thymic organ cultures induces IL-10 and transforming growth factor ␤, cytokines not studied here, and thereby upregulates the expression of CCR5.…”
Section: Discussionsupporting
confidence: 53%
“…However, in our ex vivo tissues, no infection with any of the primary R5 HIV-1 isolates affected the levels of the 16 measured cy- tokines/chemokines. Earlier, similar results were reported for an R5 laboratory strain and for recombinant viruses carrying R5 Envs, whereas an X4 strain significantly changed chemokine release (9,27). However, one recent study (8) has suggested that R5 HIV-1 infection of fetal thymic organ cultures induces IL-10 and transforming growth factor ␤, cytokines not studied here, and thereby upregulates the expression of CCR5.…”
Section: Discussionsupporting
confidence: 53%
“…VSV-Gmediated entry is predominantly endocytic rather than the virus cell fusion mechanism of the CD4 route. 31 This may have some influence on subsequent transcriptional activity, 32 as we have previously shown that blocking downstream receptor signaling may affect infectivity. 33 However, recent data suggest that entry using VSV-G does not influence integration site selection compared with entry via CCR5 receptor-mediated fusion (F Bushman, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…We also quantified the unspliced tat/rev/nef mRNA transcripts, transcribed during the elongation process that follows the initial transcription process (26). A reduction in viral elongated transcripts was observed after silencing of all MED subunits (Fig.…”
Section: Effect Of Mediator Complex On Viral Transcription-becausementioning
confidence: 99%
“…Gene expression assays for all analyzed human genes were purchased from Invitrogen. For viral RNA quantification, the following primers and probe amplifying tat/rev/nef mRNA were used: forward 5Ј-GGATCTGTCTCTGTCTCTCTCTCCACC-3Ј, reverse 5Ј-ACAGTCAGACTCATCAAGTTTCTCTATCAAAGCA-3Ј, and the dual-labeled fluorescent probe FAM 5Ј-TTCCTTCG-GGCCTGTCGGGTCCC-3Ј TAMRA (26). TAR transcripts were quantified with the following primers and probe: forward 5Ј-GGGTCTCTCTGGTTAGA-3Ј, reverse 5Ј-GGGTTCCCT-AGTTAG-3Ј, and the probe that is complementary to the TAR loop region of the HIV-1 LTR and also dual-labeled, FAM 5Ј-GCCTGGGAGCTCTCTGG-3Ј TAMRA (27,28).…”
Section: Cells-tzm-bl and Hek293t Cells (Aidsmentioning
confidence: 99%